The structure of the computational signal algebra and its application in digital image processing (2011)
This work starts from the knowledge of the mathematical structure of the signals space used in signal processing and provides the development of a computational theoretical framework of signal algebra for modeling and processing applications using digital images. The mathematical structures were implemented over computational structures using the Java programming language as a tool for the coding of the algorithms. The implemented tool was called JCID (Java Computational Image Developer), which allows for one to implement several of the operators from the signal algebra for one-dimensional and two-dimensional signals, and the creation of new entrants through the composition of the basic operators.